The Implementation of Entrepreneurship Values in Sprachbeherrschung Learning Based on Local Wisdom - Tamaela, Ida C.; Soumokil, Piet; Apituley, Patresia S. (KnE Social Sciences, 2024)
This research was conducted on Sprachbeherrschung learning in the German Language Education Study Program, FKIP-Unpatti. This study aimed to implement the value of entrepreneurship in German language learning based on local wisdom and also to shape the students’ character by instilling values such as independence, creativity, risk-taking, and responsibility. Students are not only trained with knowledge and theories in textbooks, but in the learning process students are instilled with entrepreneurship values, which consist of five aspects, namely: (a) the learning process of Sprachbeherrschung; (b) the cultivation of entrepreneurship value through group roles; (c) the impact of the implementation of entrepreneurship value on learning outcomes; (d) the feasibility of dividing roles into groups; and (e) the effectiveness of learning Sprachbeherrschung based on local wisdom. The instrument is a questionnaire which was then analyzed using descriptive analysis method. Previously, the validity and reliability of the questionnaire had been tested and the test results stated that all statement items in the questionnaire were valid and the questionnaire was reliable. Based on the analysis results, it is shown that 60% of respondents agreed on the aspects of the Sprachbeherrschung learning process, 50% of respondents agreed on the aspects of instilling entrepreneurship values through group roles, 70% of respondents agreed on the aspects of the impact of the implementation of entrepreneurship values on learning outcomes, 90% of respondents agreed on the aspects of the feasibility of dividing roles in groups, and 70% of respondents agreed on the aspects of the effectiveness of local wisdom-based Sprachbeherrschung learning. Furthermore, the average value of each aspect was calculated and it was found that the five aspects had an average value that fell into the agreed category. Keywords: entrepreneurship value, Sprachbeherrschung learning, local wisdom